Croplife Europe Virtual Conference 2021: Sustainable Solutions to Protect Crops. (1st April 2021) - Blake, Robin
This event was the first to be organised by CropLife Europe, formerly known as the European Crop Protection Association (ECPA), and was held virtually from 9th to 11th March 2021. The focus of the meeting was the current and future challenges in the implementation and application of Regulation (EC) 1107/2009, and followed the successful regulatory conferences previously organised by ECPA and held each year in Brussels, Belgium. This article summarizes Day 1 and 2 of the conference.